Recent discourses on vigilantism within South Africa - O'Reilly, Ciaran (Department of Public Law, 2018)
Reports of vigilantism are common in South African media today, where it is portrayed as a growing trend of reactionary violence against the perception of a high crime rate in the country and a criminal justice system which is failing the public. At the same time, the South African Police Service has positioned itself as taking measures to combat the high level of crime which has been blamed for this vigilantism, and publicly denouncing those who take the law into their own hands, both through comments in the media and their own press statements. This dissertation will provide an overview of the three major discourses on vigilantism in South Africa; within academic literature, the media and public arena, and from the South African state itself. In doing so, I hope to contribute to the understanding of how vigilantism is depicted, described and discussed in South Africa today.